Optimasi Sintesa Nanokoloid Human Serum Albumin sebagai Agen Limfoskintigrafi Menggunakan Central Composite Design-Response Surface Methodology - Lestari, Wening; Setiyowati, Sri; Triningsih, Triningsih; Asyikin, Khoirunnisa Fauziah; Suharmadi, Suharmadi; Mujamilah, Mujamilah; Sulungbudi, Grace Tjungirai; Juliyanto, Sumandi (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
The prevalence of cancer in Indonesia is increasing and various cancer treatments still have shortcomings, cancer recurrence still occurs. Lymphoscintigraphy is a method for detecting disorders of the lymphatic system, which are closely related to cancer cells. Human serum albumin nanocolloid as a lymphoscintigraphic agent consists of particles measuring